A simplistic way for cooling asphalt mixture using a modified sand mixture and low thermal absorptivity materials - Khadrawi, A. F.; Saad Abo-Qudais; Al-Nimr, M.A. (Universiti Malaysia Perlis, 2009)
Organized by School of Mechatronic Engineering (UniMAP) & co-organized by The Institution of Engineering Malaysia (IEM), 11th - 13th October 2009 at Batu Feringhi, Penang, Malaysia.